Analisis Upaya Pemerintah Desa dalam Penanganan Masalah Stunting di Desa Pagomogo Kecamatan Nangaroro Kabupaten Nagekeo - Maria Rosandi Dua Ani; Jacob Wadu; Belandina L. Long; Rafi A. Kholikin (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The problem of stunting is still a serious issue in health development in Indonesia because it has an impact on the quality of human resources. This study aims to analyze the efforts of the Pagomogo Village Government in handling stunting. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Informants were determined using purposive sampling consisting of village governments, health workers, cadres, and the community. The results of the study show that the village government has implemented various programs, such as Supplementary Feeding (PMT), strengthening Human Development Cadres (KPM), improving services through community institutions, and sanitation development. However, the implementation of the program has not been optimal because it is still constrained by economic factors, low public awareness, limited counseling, and access to clean water. This study concludes that the main problem does not lie in the availability of programs, but in the implementation and sustainability aspects. Therefore, it is necessary to strengthen community empowerment, improve education, and evaluate results-based programs.